Three-dimensional seismic response analysis of connected structures with damping layers - Chenghao Xu; Dewen Liu; Kangjie Ling; Xiaopeng Li (PLoS ONE, 2026)
To enhance the seismic damping effect of connected structures under intense seismic activities, this study introduces a novel control system for connected structures. This system strategically places the damping layers at different locations within the main towers to mitigate the violent system response of the connected structure during rare earthquakes. The double-sided damping structure mainly involves arranging damping layers in the towers on both sides of the connected structure. The damping layers use lead-core isolation bearings (LRB), which fully combines the concepts of damping and isolation. It applies isolation technology to the damping system of high-rise structures, and can effectively solve the technical problem of overturning when isolation technology is applied to high-rise buildings in engineering experiments. The structure is modeled using ABAQUS. Models for both single-sided and double-sided damping structures are established and subsequently compared with the seismic resistance structure. This comparison is conducted to analyze the time-history response of layer shear, base reaction force, top-layer acceleration, and interstory drift of various structural models under rare earthquakes. Additionally, shear-drift hysteresis curves of the damping layer are constructed to evaluate the energy dissipation rate of the structure’ s damping layer using an energy analysis method. The results show that both damping structures exhibit superior energy dissipation and damping effects. However, the introduction of an additional damping layer in the double-sided damping structure results in a more obvious damping effect and a higher energy dissipation rate. The risk of overturning due to excessive bending deformation of the superstructure is mitigated by designing the location of the damping layer. However, the control effect of both damping structures on vertical earthquakes is not obvious, and further research is needed.